Palaeobiology of the Medieval Population of Albano (Rome, Italy): A Combined Morphological and Biomolecular Approach. (15th May 2013) - Ciaffi, R.; Lelli, R.; Müldner, G.; Stantcheva, K.; Fischetti, A. L.; Ghini, G.; Craig, O. E.; Milano, F.; Rickards, O.; Arcudi, G.; Martínez‐Labarga, C.
Abstract Recent years have seen increased interest in skeletal populations from the Imperial Roman Age in Italy, but much less is known about diet and standards of living in the subsequent medieval period. To fill this gap, we conducted a morphological analysis of human remains from Albano, an Italian town near Rome, as well as a stable isotope analysis of bone collagen to reconstruct diet. The sample was recovered from a Medieval cemetery (1040–1220 cal. yr. BP) located in the gardens of the historical Palazzo Doria Pamphili in Albano. A minimum number of 40 individuals (31 adults and 9 sub‐adults) were examined using standard methods. Though the general health status of the population was good, signs of cribra orbitalia and diffuse enthesopathies were noted during the morphological examination. Stable carbon and nitrogen isotope analyses of the bone collagen from 24 adult humans and three faunal bones indicate that the diet of the population may be described as predominantly terrestrial and C3‐plant based although the data for some of the individuals suggest a modest consumption of C4‐(millet) based or aquatic proteins. No evidence of significant dietary differences between the sexes was found. The comparison of the isotope data from Albano with those from populations recovered in the same region is consistent with a shift from a terrestrial, possibly plant foods‐dominated subsistence in the Early Middle Ages to a diet with a higher contribution from animal proteins, both terrestrial and aquatic, in the Later Middle Ages. Copyright © 2013 John Wiley & Sons, Ltd.